Data & telecommunications dictionary - Petersen, Julie K (Boca Raton : CRC Press, 1999)
"Data & Telecommunications Dictionary improves on current references through its encyclopedic format with clearer, easier-to-read layout and illustrations; greater technical and historical accuracy; coverage of new satellite technologies; coverage of network protocols and emerging fiber optic media; inclusion of telecommunications standards bodies and associations; origins of historic technologies leading to the computer revolution; capsule biographies of significant contributors to telecommunications; and over 300 charts, photographs, and illustrations."--Jacket.
Includes bibliographical references (pages 804-805)
Keywords: Telecommunication -- Dictionaries; Data transmission systems -- Dictionaries; Computer networks -- Dictionaries